FKAAB Laboratory Booking System - Mohd Nazri, Nurul Athirah; Mohamad, Radiah (Applied Information Technology And Computer Science, 2024)
The Faculty of Civil Engineering and Built Environment (FKAAB) faces inefficiencies and transparency issues in its manual reservation system. This project aims to develop a user-friendly, web-based system, revolutionizing resource management. Using a prototype, the contemporary system is designed, employing a data-driven methodology for informed judgments and improved resource allocation. Key objectives include simplifying reservations, increasing efficiency, and ensuring system stability. Anticipated benefits encompass enhanced efficiency, transparency, and reduced processing time for laboratory facilities. The initiative serves as a model for resource management, enhancing data-driven decision-making and FKAAB's competitiveness. The system's design prioritizes sustainability, offering a disruptive solution to recurrent resource management issues, potentially improving FKAAB's efficiency and academic reputation. Future work involves testing and adaptation to changing academic needs.